PENGUATAN KAPABILITAS BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) PROVINSI RIAU DALAM PENANGGULANGAN KABUT ASAP TAHUN 2015 - Rizki Alta Edison; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Strengthening Capabilities Regional Disaster Management Agency of Riau Province (BPBD) in tackling the haze problem in 2015. The author identifies himself as the 2015 disaster Riau province experienced tremendous smog. In addition the haze itself from 1997 is always present in the province of Riau. BPBDs itself is a government agency engaged in the disaster area have an important role in disaster management, the reality is not able to cope with this disaster. The problem of this research is How the capabilities of regional disaster management agencies Riau Province in tackling the haze in 2015 ?, and what obstacles or barriers capability of disaster management agencies in the response area of Riau Province haze in 2015 ?. INIA research purposes dalah know the capabilities of local disaster management agency Riau Province in tackling the haze in 2015 and knowing the obstacles or barriers capability of disaster management agencies in the response area of Riau Province in 2015 smog.The research method in this thesis is qualitative research. In collecting the data, researchers use interviewing techniques, observation, and documentation. By using key informants as a source of information and use some of the questions the source of information by looking at the phenomena contained in the data legally.Based on these results it can be concluded that the regional disaster management capability Agency (BPBD) of Riau Province in tackling the haze in 2015 of the four criteria of capability administrations of three criteria is not going well. While a good run capability. While the four obstacles or barriers capabilities BPBDs Riau Province in tackling the haze in 2015 can be said to fully experience all obstacles.Keywords: Strengthening Capabilities, Countermeasures, Haze